Interferon-Induced Protein With Multiple Tetratricopeptide Repeats 3 Is Associated With Response to Chemotherapy and Recurrence but Not With Survival. Issue 10 (November 2020) - Popp, Marie Christine; Klippstein, Maximilian; Lohneis, Philipp; Kalinski, Thomas; Li, Jiahui; Quaas, Alexander; Bludau, Marc; Wang, Zhefang; Waldschmidt, Dirk; Kunzmann, Volker; Damanakis, Alexander; Gebauer, Florian; et al.
Abstract : Objectives: The interferon-induced protein with multiple tetratricopeptide repeats 3 (IFIT3) seems to be associated with the prognosis in pancreatic cancer. Here we clarify whether the heterogeneity of IFIT3 expression affects previous IFIT3 analysis. Methods: This retrospective study analyzes pancreatic cancer tissue samples retrieved by surgery from 2 independent patient cohorts. Patients underwent either primary surgery (n = 72) or received neoadjuvant chemotherapy (n = 12). Immunohistochemistry assessed IFIT3 expression and its heterogeneity. Complementarily, we analyzed publicly available transcriptomic data (n = 903). Results: Of the primarily resected tumors, 16.4% were heterogeneous. Patients with IFIT3-negative tumors did not survive longer compared with patients with IFIT3-positive tumors. An analysis of publicly available data confirmed this result. Patients developing lung metastases had the best prognosis (4.8 years) with significantly lower IFIT3 expression compared with liver metastasis ( P = 0.0117). Patients receiving neoadjuvant therapy who are IFIT3 negative had a longer disease-free survival (1.2 vs 0.3 years, P = 0.0081). Conclusions: Low IFIT3 expression is not associated with longer survival. Divergent results from tissue microarray analyses could be explained with tumor heterogeneity. As a single biomarker, IFIT3 is not suitable for predicting disease prognosis. Recurrence of lung metastases and response to neoadjuvant chemotherapy are associated with low IFIT3 expression. Abstract : Supplemental digital content is available in the text.